Soft-Capitalism: Business Revitalization Based on Spirituality - Umam, Saiful; Kalsum, Afif Umi (KALAM, 2020)
Soft capitalism has begun to spread in Indonesia, marked by the number of Islamic businesses that are developing. This raises questions about the Islamic economic system and capitalism which seem to merge without any obstacles. In Yogyakarta, this phenomenon can be found in the Geprek Chicken and Milk (Preksu) and Waroeng Steak which is a popular economic movement in the culinary field. Specifically, from the business object, the author conducts indepth study at how the two paradigms that tend to be contradictory, capitalism and Islam, are able to go hand in hand in their manifestation based on the spiritual company. This study using the sociological approach and literature study and primary data based on field observation. The result shows that the fusion between Islamic values and capitalism produces a new phenomenon influenced by a strong moral economy from producers (entrepreneurs) and high consumer enthusiasm sustained by the role of new media. Therefore, the author argues that the growing moral value of human economies finally shatters egocentricity capitalist and Islamic is necessary as a measure of decorum (ethical) in the economy.